2021
DOI: 10.1080/02813432.2021.1973250
|View full text |Cite
|
Sign up to set email alerts
|

Impediments to and impact of checklists on performance of emergency interventions in primary care: an in situ simulation-based randomized controlled trial

Abstract: Objective: Medical crises occur rather seldom in the primary care setting, but when they do, initial management impacts on morbidity and mortality. Factors that impede the performance of emergency interventions in primary care have not been studied through in-situ simulation. Checklists reportedly improve crisis management. Design: This randomized controlled trial evaluated emergency intervention performance during two scenarios (hypoglycemia-coma and anaphylaxis-cardiac arrest) simulated at primary care cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…For the important outcome of adherence to a protocol or process, we identified very low certainty evidence (downgraded for very serious risk of bias and serious imprecision) from four RCT. 13 , 38 , 39 , 40 Two studies 13 , 38 with a total of 79 participants in each of the intervention and control groups demonstrated highly significant increases in average performance scores 38 and reduced failure to adhere to critical steps. 13 Two studies 39 , 40 with 607 participants in 85 teams in the intervention and 95 teams in control groups demonstrated that using a medical emergency checklist resulted in 9% absolute and 15% relative risk reduction of failure to adhere to guideline-adherent critical process steps.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the important outcome of adherence to a protocol or process, we identified very low certainty evidence (downgraded for very serious risk of bias and serious imprecision) from four RCT. 13 , 38 , 39 , 40 Two studies 13 , 38 with a total of 79 participants in each of the intervention and control groups demonstrated highly significant increases in average performance scores 38 and reduced failure to adhere to critical steps. 13 Two studies 39 , 40 with 607 participants in 85 teams in the intervention and 95 teams in control groups demonstrated that using a medical emergency checklist resulted in 9% absolute and 15% relative risk reduction of failure to adhere to guideline-adherent critical process steps.…”
Section: Resultsmentioning
confidence: 99%
“… 13 , 38 , 39 , 40 Two studies 13 , 38 with a total of 79 participants in each of the intervention and control groups demonstrated highly significant increases in average performance scores 38 and reduced failure to adhere to critical steps. 13 Two studies 39 , 40 with 607 participants in 85 teams in the intervention and 95 teams in control groups demonstrated that using a medical emergency checklist resulted in 9% absolute and 15% relative risk reduction of failure to adhere to guideline-adherent critical process steps. All teams had a lower failure rate for adherence to key processes with the intervention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Training programs for multidisciplinary teams 4,11,12,22,32,39,[53][54][55][56]95,106,107 using ISS have been shown to effectively improve the technical and non-technical skills of health professionals for managing emergency situations, in addition to optimize learning, both at individual's and team's levels 90 . Thus, ISS can be valuable to improve patient safety, as it allows the practice of care team dynamics within a real clinical environment 4 .…”
Section: Thematic Area Total Participantsmentioning
confidence: 99%
“…In this context, effective learning strategies such as simulation‐based training may serve as an additional resource to foster an educated, occupational health‐competent and motivated nursing workforces (Vaquero‐Álvarez et al, 2020). Nursing simulation has been used to improve the quality of patient care in assorted real‐life scenarios in primary care, such as hypoglycaemia‐coma and anaphylaxis‐cardiac arrest or suicidal attempts, by providing nursing students and health care professionals with clinical skills, critical and problem‐solving thinking (Dryver et al, 2021). A number of studies have attempted to understand nursing students' experiences and perceptions with simulation as a learning method, outlining confidence, independence and active participation as deciding attributes that make simulation a truthful representation of the clinical reality to which students will be exposed in the long term (Bø et al, 2021; Mulli et al, 2022; Saaranen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%